(untitled) (Interdisciplinary Studies Journal, 2024)
This work corresponds to the unfolding of an intellectual effort bringing together researchers from different fields of knowledge within the scope of a research project on the theme of social banditry that culminated in the publication of a collection with some of the main cases that occurred in southern Brazil. Based on a literature review, the text is structured in such a way as to establish interdisciplinary interfaces between different dimensions, domains and theoretical-methodological approaches according to which the historiographical perspective is privileged. As a whole, this work presents possibilities for the use of theoretical and methodological resources that, highlighted or combined, indicate paths for conducting research on social banditry.